RACIAL STRATIFICATION OF AFRICAN-AMERICAN CHARACTERS IN TATE TAYLOR'S THE HELP (Universitas Pamulang, 2019)
This study is purposed to uncover strengthening racial stratification done by African-Americans characters in a film, entitle The Help, written and director by Tate Taylor. This movie portrays the life of black maids who suffering racial stratification conducted by white women in Jackson Mississippi during the 1960’s. This study seeks to argue that the strengthening of African-American characters in this film highlights the racial attitude from the white women attitude. To analyze this film, a concept of racial stratification by Martin N. Marger is applied. The result of this study shows that the African-American characters in The Help strengthening their racial stratification for being diversity of appearance and diversity of class social. Taylor shows that the racial stratification is shown by white women who separate their social class as employers from black women who are maids. The maids get many differences of the facilities and attitude from their employers.Keywords: racial stratification, African-American, The Help.